Traditionalism in African local government : with special reference to the Transkei and Lesotho - Kotzé, D. A.(Dirk Albertus),1939- (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1968.